2017
DOI: 10.14348/molcells.2017.0106
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Diversity Determination, and Application to Antibody Selection of a Human Naïve Fab Library

Abstract: We constructed a large naïve human Fab library (3 × 1010 colonies) from the lymphocytes of 809 human donors, assessed available diversities of the heavy-chain variable (VH) and κ light-chain variable (VK) domain repertoires, and validated the library by selecting Fabs against 10 therapeutically relevant antigens by phage display. We obtained a database of unique 7,373 VH and 41,804 VK sequences by 454 pyrosequencing, and analyzed the repertoires. The distribution of VH and VK subfamilies and germline genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…These libraries are generated from healthy donor's mRNA or RNA without bias toward a particular disease state, and are used to yield mAbs against unlimited range of antigens ( 151 ). To generate a highly diverse naïve antibody phage library, it is recommended to use a large pool of donors from diverse ethnic groups, and to maximize the efficiency of antibody gene amplification in the process of library construction ( 152 155 ).…”
Section: Types Of Antibody Phage Display Librariesmentioning
confidence: 99%
“…These libraries are generated from healthy donor's mRNA or RNA without bias toward a particular disease state, and are used to yield mAbs against unlimited range of antigens ( 151 ). To generate a highly diverse naïve antibody phage library, it is recommended to use a large pool of donors from diverse ethnic groups, and to maximize the efficiency of antibody gene amplification in the process of library construction ( 152 155 ).…”
Section: Types Of Antibody Phage Display Librariesmentioning
confidence: 99%
“…The percentage expression (or display) was calculated based on the number of clones with an OD (optical density) over three-fold the background in an ELISA (Enzyme-Linked ImmunoSorbent Assay) for periplasmic expression of Fab or scFv. Kim et al [28] reported as functional ORFs those sequences with no stop codons; they did not report the expression nor display before the selections. The authors of pIX V3.0 [29] estimated the percentage of ORFs as sequences without stop codons and functionality as Fab display in an ELISA.…”
Section: Effective Size Of the Phage Display Antibody Librariesmentioning
confidence: 99%
“…It combines kappa (HAL10) and lambda (HAL9) light chains displayed as scFvs. The fourth and most recently published naïve library [28] was developed at Kangwon National University (KNU). It only contains kappa-type light chains, and thus we called it KNU-Fab.…”
Section: Types Of Antibody Repertoiresmentioning
confidence: 99%
“…For natural naive libraries, the general paradigm has been to increase the natural source of B-cell diversity by increasing the number of donors 23 , 25 , 26 . The question remains as to whether increasing the number of donors actually leads to improved antibody diversity and library functionality.…”
Section: Introductionmentioning
confidence: 99%